Caracterização radiométrica orbital da ferrugem e da fenologia do cafeeiro em diferentes sistemas de irrigação - Pires, Miryan Silva de Oliveira (2018)
Brazil is the main coffee producer, and Minas Gerais is the state that contributed most to this important crop in agribusiness. Arabica coffee (Coffea arabicaL.) may have its production compromised by several factors, such as coffee rust (Hemileia vastatrixBerk. & Br.) which can cause serious damage to the crop. Another factor to know is the phenology of the plant that is important to identify the necessary activities in the management and cultural treatments of the crop. A tool to assist in the management of coffee cultivation is remote sensing using satellite images, such as the Landsat mission, associated with the geographic information system (GIS) for digital processing. The objective of this study was to evaluate the applicability of coffee crop monitoring under different irrigation systems by orbital radiometry, characterizing the spectral, spatial and temporal patterns of rust and coffee phenology. In the first study, orbital imaging products were used and correlated with the data of coffee rust incidence collected in the field. The lower near infrared (NIR) reflectance values corresponded to the higher values of coffee rust incidence, and, irrigated areas and rainfed area presented different behaviors in the short-wave infrared 1 (SWIR-1) and short-wave infrared 2 (SWIR-2) regions. In the second study, false color and natural color composition maps were used for visual interpretation of the crop, associated to data collected in the field. It was possible to analyze the characteristics of the coffee phenological phases and aspects of the different environments, as well as the presence of biennial coffee productivity.